Estimating time travelling for flood from upstream to downstream using Muskingum method : Sungai Kuantan, Pahang Darul Makmur - Farah Norhazrina, Rosli (2012)
The social disruption caused by floods can seriously undermine the quality of life of individuals and impact on the fabric of affected communities (Gordon, 2004). As well as the physical and health dangers of flood waters, the psychological impact of the emergency and aftermath causes longer term effects that may be exacerbated by stresses such as having to move out of the home, cleaning up, negotiating with insurers and getting damage repaired and goods replaced ( RPA, 2005). Muskingum method is a non-structural measure that helps in prevention of occurrence of flood. From Muskingum method, the lag time (At) when the flood is going to occur is predicted. The existence of the Chereh dam plays a major role in delaying the time taken for the water flow to the downstream, which in 2001 (before the construction of Chereh dam) the lag time is one day and there is an increase of lag time in 2011 (post construction) which is two days. Chereh dam is very effective for the flood mitigation. By using the same method, the lag time (At) is also being determined for the residential that is situated along Sungai Kuantan, where the lag time (At) for Kg Bayas, Kg Batu Enam, Kg Nada and Kg Sungai Cam is two days. As for Kg Kuala Reman, Kg Ah Tong, Kg Bala Sawar and Kg Permatang Badak are three days. The information provided by early warning systems (Lag time (At)) enables authorities and institutions at various levels to immediately and effectively respond to a disaster where the planning of the executed plan could be done before it is too late.